Using risk simulation to reduce the capital cost requirement for a programme of capital projects - Joubert, Francois; Pretorius, Leon (Business, Management and Economics Engineering, 2017)
This paper combines various concepts related to (i) project risk management, (ii) Monte Carlo simulation, (iii) project contingency cost estimation, and (iv) the relationship between project and programme risks, to illustrate that the contingency requirements are lower when simulating all the risks in the programme when comparing it with the individual project contingency requirement. A case study organisation provided 86 quantified risk registers related to port and rail capital projects. For each of these risk registers, the project contingency was estimated using a prescribed risk register template and Monte Carlo simulation software. The same 86 quantified risk registers were then used to simulate the programme contingency. The simulation results indicated that the programme contingency requirement was approximately 8% points lower than that of the sum of the individual projects. The first implication of this research result is that, should borrowed capital be used to fund the projects, the interest bill would be higher when calculating project contingency on a project-by-project basis. The second is that regularly appearing low probability, high impact risks, should be identified and these risks should be quantified not in the projects themselves, but in a centrally managed, programme cost contingency fund.